ELECTRIC VEHICLE (EV) POWER CONSUMPTION (BATTERY) ON UPHILL ROAD CONDITIONS - Suksmadana, I Made Budi; Satiawan, I Nyoman Wahyu; Wiryajati, I Ketut; Warindi, Warindi; Supriyatna, Supriyatna; Supriono, Supriono; Citarsa, Ida Bagus Fery (DIELEKTRIKA, 2023)
Electrical Vehicle (EV) has been developing since the mid-18th century and reached its peak at the end of the 18th century. Dwindling fuel reserves and environmental damage caused by exhaust emissions from millions of fossil-fuel vehicles are the driving factors for the development of electric cars, technological developments in the battery sector have also contributed to the development of electric cars. One of the important components in an electric car is the battery which will provide resources to the system, so determining the capacity and knowing the performance of the battery used is very important. To find out the battery performance, the model can be made using MATLAB/SIMULINK. The model built consists of electric (DC motor, control and battery) and mechanical (transmission, wheels, brakes and body) parts. Of the models made for speeds of 35, 40, and 45 kmph on level ground, the distances that can be covered are 2,292, 2,597, and 2,899 m, while the remaining battery capacity (SoC, %) is 92.93%, 91.16%, and 89.17%. This is proportional to the distance traveled which also proves that the model made is appropriate. Uphill roads affect the use of battery capacity, the greater the angle of incline, the greater the battery capacity used.